2011
DOI: 10.1152/ajpheart.01000.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor blockade improves diastolic function independent of blood pressure reduction in a transgenic model of RAAS overexpression

Abstract: Habibi J, DeMarco VG, Ma L, Pulakat L, Rainey WE, WhaleyConnell AT, Sowers JR. Mineralocorticoid receptor blockade improves diastolic function independent of blood pressure reduction in a transgenic model of RAAS overexpression. Am J Physiol Heart Circ Physiol 300: H1484 -H1491, 2011. First published January 14, 2011; doi:10.1152/ajpheart.01000.2010.-There is emerging evidence that aldosterone can promote diastolic dysfunction and cardiac fibrosis independent of blood pressure effects, perhaps through increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 48 publications
(137 reference statements)
7
42
0
1
Order By: Relevance
“…29 However, the clinical evidence supporting a role of aldosterone and MR activation in the development of LV diastolic dysfunction is weak and mostly suggested by findings of studies conducted with MR antagonists in patients with heart failure and preserved ejection fraction or hypertensive patients with diastolic dysfunction. Mottram et al 15 reported beneficial effects of low-dose spironolactone on myocardial relaxation in 30 treated hypertensive patients with exertional dyspnea and abnormal LV filling patterns.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, the clinical evidence supporting a role of aldosterone and MR activation in the development of LV diastolic dysfunction is weak and mostly suggested by findings of studies conducted with MR antagonists in patients with heart failure and preserved ejection fraction or hypertensive patients with diastolic dysfunction. Mottram et al 15 reported beneficial effects of low-dose spironolactone on myocardial relaxation in 30 treated hypertensive patients with exertional dyspnea and abnormal LV filling patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Restraint conditioning was initiated before blood pressure measurements were performed as previously described [14,30]. SBP was measured in triplicate on separate occasions throughout the day using the tail-cuff method (Harvard Systems, Student Oscillometric Recorder) prior to initiation of treatment and on days 19 or 20 and prior to sacrifice at 21 days.…”
Section: Methodsmentioning
confidence: 99%
“…SBP was measured in triplicate on separate occasions throughout the day using the tail-cuff method (Harvard Systems, Student Oscillometric Recorder) prior to initiation of treatment and on days 19 or 20 and prior to sacrifice at 21 days. Urine albumin and creatinine were determined as previously described [14,30]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations